(untitled) (Tribhuvan University Journal of Microbiology, 2021)
Objectives: The study was aimed to identify potential bacterial pathogens from the panipuri samples collected from different vendors of Bhaktapur district and determine their antibiogram patterns. Methods: Altogether 120 (40 puri, 40 stuffing and 40 pani) samples of panipuri were collected from different vendors of Bhaktapur district in a cold chain and were transported to the microbiology laboratory. Puri and stuffing were then pre-enriched, enriched and cultured while pani samples were processed using the MPN method. All the isolates were identified following standard microbiological procedure and subjected to antibiotic susceptibility testing following CLSI guidelines. Results: The result revealed contamination of 77.5% stuffing, 67.5% puri and 52.5% pani samples with pathogenic bacteria. Among bacterial pathogens, the highest number was Staphylococcus aureus followed by Escherichia coli and Salmonella spp. 100% of S. aureus were found to be resistant to ampicillin and novobiocin. Similarly, 94.1% of E. coli were resistant to ampicillin followed by ciprofloxacin (64.7%). A very few isolates of Salmonella spp, Shigella spp and Vibrio spp were resistant to tetracycline. The highest number of multidrug-resistant bacteria were S. aureus, followed by Klebsiella spp and E. coli. Conclusion: The study showed that the panipuri samples from street vendors were found to be highly contaminated with pathogenic bacteria which might affect consumers’ health. Thus, to prevent any food-borne illness in the future, frequent evaluation and regulation of the quality of such foods should be carried out.